Can providing daily iron-fortified lunches to school-going children living in an impoverished Guatemalan community improve iron status? - Llesenia Massey; Steven McGeehan; Manichanh Ratts; Thomas Mitchell; Christopher Cotten; Alejandra Perez; Kathy Beerman (Journal of Global Health Reports)
# Background